MABAC Method Dalam Penentuan Kelayakan Penerima Bantuan SPP - Wina Yusnaeni; m marlina (Universitas Bina Sarana Informatika, 2020)
Acceptance of elementary school students, first level, level of preventive and tertiary levels are conducted annually. In conducting the registration, there are requirements that must be filled by the prospective registrant. Criteria determined by the school in which the scholarship registrant data will be in the data by the school. Scholarships are financing given by the government, agencies or schools, which do not originate from self-financing or parents. Scholarships are given to those who are entitled to receive because they have quality, and achievement as a scholarship recipient. In the logging of the Committee, one by one and conducted surveys and decisions from the Committee. The need for time in input and decision only by the Committee does not guarantee the decision to be taken precisely and accurately. Therefore, the need for a decision support system that can help determine the results more objective according to the criteria that have been specified. One of the methods discussed by the author here MABAC Method. There is stability in the solution and rational than some other methods of decision support system. The use of methods is conducted against 128 applicants with predefined criteria data. From the data is determined the weight of the assessment and the alternative weight of criteria that produce decent not like students receive scholarships or SPP assistance.